1998
DOI: 10.1007/s004490050544
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of microcarrier cell culture processes in one hundred mini-liter spinner flask and fifteen-liter bioreactor cultures

Abstract: Microcarrier cell culture process can be used to culture anchorange-dependent cells in large bioreactor vessels. The process performance in large bioreactors is usually less prominent than that in spinner¯ask vessels and bench scale reactors. In this study we investigated the microcarrier cell culture processes in 100 ml spinner¯ask and 15-liter bioreactor cultures, including the kinetics for cell attachment, cell growth and the production of Japanese encephaltilis vaccine strain (Beijing-1) virus. Under a ®xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Wu et al, 10 who investigated Vero cell growth on Cytodex1 microcarriers, found a close correlation between decrease in suspension cell number and increase in cells attaching to microcarriers. This is in opposite to our findings with significantly different kinetic constants k sus and k at under all cultivation conditions.…”
Section: Attachment Behaviormentioning
confidence: 91%
See 3 more Smart Citations
“…Wu et al, 10 who investigated Vero cell growth on Cytodex1 microcarriers, found a close correlation between decrease in suspension cell number and increase in cells attaching to microcarriers. This is in opposite to our findings with significantly different kinetic constants k sus and k at under all cultivation conditions.…”
Section: Attachment Behaviormentioning
confidence: 91%
“…The same result was found by Forestell et al 6 for MRC-5 cells. Ng et al, 8 Wu et al, 10 and Hu et al 11 showed that attachment rate on Cytodex1 microcarriers was highest at a pH of 7.1-7.2, whereas attachment to uncharged macroporous Cultisphere microcarriers was unaffected by changes in pH value over a wide range. At the optimum pH, the higher electrostatic forces of the positively charged Cytodex1 microcarriers probably reduced detachment of nonspreading cells from the microcarriers' surface.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…For this reason, the growing of cells in MCs is widely used to obtain the vaccine viruses such as rabies ( Frazzati-Gallina NM et al 200;Mendonça RZ et al 1993 ), chicken viruses (43), Japanese encephalitis virus ( Wu SC, Huang Gyl. 2000;Wu S-C et al 1998 ), measlesvirus (Mendonça RZ et al 1994 ), varicella virus ( Chun BH, Chung SI. 2001 ), bovine respiratory syncytial virus ( Moran E. 1999 ).…”
Section: Discussionmentioning
confidence: 99%